OPEN SKY POLICY DAN STRATEGI PEMANFAATAN RUANG UDARA INDONESIA - Zidane Haikal Senoaji; Anang Setiyawan (Universitas Islam Syekh Yusuf, 2021)
The Asean open sky policy will have logical consequences on the regulation, control and utilization of Indonesian air space, therefore a strategic regulation, control and utilization strategy is needed to maintain the national interests of the Indonesian state as a whole.This paper uses doctrinal research methods through literature study, while the data analysis uses qualitative methods. The results of this research study indicate that the government must improve and make improvements to infrastructure on national aviation in terms of capacity, systems and technology, as well as strengthening existing policies and regulations so as to maximize the use and utilization of the potential of the air space.